Dynamic duos - Moore, David (New York : Scholastic, 1998)
Contains profiles of nine pairs of basketball players who make their teams stronger by working as a pair instead of as individuals.
6.6
3-6
Keywords: National Basketball Association -- Juvenile literature; Basketball players -- United States -- Biography -- Juvenile literature; Basketball players; Basketball players -- Biography